การออกแบบกับตัวเลข - อิศรางกูร ณอยุธยา, ศุภวิช; มาลยมาน, บุษยมาศ (Fine Arts Journal: Srinakharinwirot University, 2019)
To all appearances, Designing is all about form and function, visual elements, and design principles. Designers and educators tend to too much emphasize on the matter of visual attributes, however there are other universal principles of design that we can utilize and apply, borrowing from other relevant areas. This article will especially focus on the topic of “number” in different principles and theories, such as Fibonacci sequence, Pareto principle, Rule of third, Hick’s law, Fitt’s law, Monte Carlo simulation, 100th monkey effect, Gutenberg diagram, Einsenhower matrix, Hierarchy of needs, 5 hat racks, 6 degrees of separation, SCAMPER, Ockham’s razor, Forgiveness respectively. In order to keep up with ever changing technology and new body of knowledge, designers and posterity should be aware of these universal principles. They should be open minded and be well rounded at the same time.